Gluten characteristics imparting bread quality in wheats differing for high molecular weight glutenin subunits at Glu D1 locus - Mohan, Devinder (Physiol Mol Biol Plants, 2015)
High yielding genotypes differing for high molecular weight glutenin subunits at Glu D1 locus in national wheat programme of India were examined for bread loaf volume, gluten and protein contents, gluten strength, gluten index and protein-gluten ratio. Number of superior bread quality genotypes in four agro-climatically diverse zones of Indian plains was comparable in both categories of wheat i.e., 5 + 10 and 2 + 12. There wasn’t any difference in average bread loaf volume and grain protein content either. 5 + 10 wheats showed better gluten strength and their gluten quality was also superior in the zones where protein content was high. 2 + 10 wheats exerted more gluten due to better protein-gluten ratio. Good bread making in 5 + 10 was derived by better gluten strength and also gluten quality in certain regions but bread quality in 2 + 12 wheats was channelized through higher gluten content as they were more efficient in extracting gluten from per unit protein. Difference in route to bread quality was apparent as gluten content and gluten strength were the key gluten attributes in 5 + 10 whereas protein content and gluten index were prominent in 2 + 12 types. Unlike 2 + 12, there was a ceiling in gluten harvest of 5 + 10 wheats as higher protein failed to deliver more gluten after some limit.